Increasing Student Resilience Through Integration of Islamic Values in PAI Learning - Umam, Khoirul; Hasan, Moch. Sya'roni (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This research examines implementing extracurricular activities to improve students' non-academic achievements at Tabanan Islamic Elementary School. A qualitative approach and observation, interviews, and documentation study methods were used. The research results show that Tabanan Islamic Elementary School carries out extracurricular activities by focusing on the management stages, namely planning, organizing, implementing, and evaluating. At the planning stage, coordination meetings are held, student interests are identified, and work programs are prepared to ensure activities match student interests and school goals. Organizing involves various parties with a clear division of tasks. Implementation of activities includes continuous preparation, routine practice, and program implementation, with the important role of the supervisor guiding students. Evaluation is carried out through annual meetings to identify program deficiencies for improvement. The success of the implementation is supported by competent human resources, adequate infrastructure, a diversity of choices of sports, science and technology, arts and culture activities to develop student's talents, a role in character development, as well as motivational aspects with the presence of coaches who provide guidance and motivation. Overall, implementing extracurricular activities at Tabanan Islamic Elementary School is carried out well by management concepts and is supported by various factors to improve students' non-academic achievements through quality activities that develop students' talents, interests, and character.